Indigenous traditional knowledge of medicinal plants used for the management of HIV/AIDS opportunistic infections in Katsina State, Nigeria - Kankara, Sulaiman Sani; Ishaq Nuhu, Abubakar; Abdullahi Bindawa, Kabir; Rabi'u Haruna, Muhammad; Bello, Abubakar; Babangida Abubakar, Ibrahim (Ethnobotany Research and Applications, 2022)
Background: Medicinal plants are widely used for the management of many diseases including HIV / AIDS opportunistic infections in Katsina State, North-western part of Nigeria. The usage of those plants is, however, poorly documented. Method: An ethnobotanical study was conducted to document medicinal plants used for the management of HIV / AIDS opportunistic infections in three Local Government Areas (one from each Senatorial Zone) of Katsina State, Nigeria. Information was obtained through a semi-structured questionnaire administered to 150 respondents comprising traditional healers, herbalists, farmers and HIV / AIDS patients. Results: The survey revealed 48 plant species distributed among 44 genera and 28 families. The highest Relative Frequency of Citation was observed in Anogeissus leiocarpa (DC.) Guill. and Perr (0.75). Fabaceae represented by 11 species appeared to be the most utilised family. Highest Informant Consensus factor was observed in abnormal vaginal discharge and genital ulcer. Most of the cited species are trees that are sourced from the wild and majority of medications are prepared in the form of decoction which is taken orally. The most used plant parts were leaves (40%). Conclusion: The study revealed substantial numbers and knowledge of medicinal plants used for the treatment of HIV / AIDS related infections in Katsina State, Nigeria. Further investigations to establish the pharmacological potentials of the cited species with regard to the treatment of HIV / AIDS are highly recommended. Keywords: Ethnobotanical survey; HIV / AIDS; Opportunistic infections; Medicinal plants; Katsina state